Pengaruh Gaya Kepemimpinan, Dukungan Atasan Dan Lingkungan Kerja Pada Kinerja Karyawan Di Kios Mera - Al Fikri, Mohamad Husain Syam; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of leadership behavior, supervisor support, and work environment on employee performance at Kios Mera, Kayutangan, Malang City. The research adopts a quantitative approach, utilizing questionnaires for data collection. Respondents comprised 32 employees selected using purposive sampling techniques. Data were analyzed through multiple linear regression using SPSS software. The findings reveal that leadership behavior, supervisor support, and the work environment significantly impact employee performance, both simultaneously and partially. Strategic and communicative leadership, supportive supervisors fostering individual growth, and a conducive work environment are key factors driving improved performance. The average scores of variables indicate high levels of satisfaction with these factors, reflected in increased productivity, teamwork, and work quality. Keywords: Leadership behavior, supervisor support, work environment, employee performance, Kios Mera